O processo de latenciação no planejamento de fármacos - Chin, Chung Man [UNESP]; Ferreira, Elizabeth Igne (Sociedade Brasileira de Química, 1999)
Short review about the main aspects of prodrug design, as its objectives, applicability and importance, showing the new trends in the research for selective latent forms, namely targeted drugs.
The latentiation process in drug design
Keywords: latentiation; molecular modification; prodrug design; drug design